(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2012)
When a victim is unknown, anthropologist plays a key role in preparing biological profile. Developing such profile entitles studying remains noting genetic characteristic of shape and size, which allow estimation of age, sex, population and ancestry. Estimation of stature is considered as an important parameter in medico-legal and forensic examination. An attempt is made to find out correlation and to derive a regression formula between head length and body height in Gujarat region. The material consists of 239 students from Gujarat University. Students were selected as subject because of the easy. The age was in the range of 21 to 25 years. The length of head was measured between two craniometric points, glabella and inion. Spreading caliper was used to measure head length. Height of the subject was measured with standard height measuring instrument in anatomical position. Measurements were taken at fixed time to avoid diurnal variation. The result obtained was analysed and attempt was made to derive a formula between head length and total height of an individual. The result shows that there is a definite correlation between head length and height of an individual. In spite of the racial and ethnical variation, this formula may be a definite correlation between head length and height of an individual.